Association Between the Multiparity and Spondylolisthesis in Women 30-70 Years Old, Kohistani Physiotherapy Clinic 1394-1400 - Jamay, Fahima; Saeedi, Noria (Journal for Research in Applied Sciences and Biotechnology, 2023)
Summary: Spondylolisthesis is a common problem among those who complain of back pain and is defined as lysthesis or incomplete subluxation of one vertebra over another with different grades which is caused by unilateral or bilateral fracture of pars inter articularis or degeneration of the vertebral column. Studies show that the prevalence of this problem relates to increase age. Age 50 and above is more prone to it. Also, the incidence of this problem increases about 22% among pregnant women. But here in Afghanistan still there is not enough researches done about this. In Afghanistan the multiparity, hard physical activities during pregnancy, home deliveries are somewhat accepted phenomenon, so the incidence of lysthesis may be possible below age 50 and lots of women with multiparity who suffer from back pain may have spondylolisthesis. Study objectives and aims: The aim of this study is to find the relationship between multiparity and lumber degenerative spondylolisthesis among women aged30-70 yrs. Methodology: An analytic cross sectional study have been done on 101 female patients who referred to kohistani physiotherapy clinic for their back pain treatment years 2015-2021.the data collected from the patients record sheets and analyzed by epi info and excel programs in computer. Results: From those 101 patients 6 of them have been excluded from the research because they did not meet the inclusion criteria and 95 cases have been selected. The result of z-test show (p=0.5) which means that there is no direct relation between multiparity and degenerative spondylolisthesis. The grade 1 spondylolisthesis has more idiopatic factor than grade 2 and 3. Finding shows 3.4 times. Conclusion: According to our findings we can say that there is not direct association between multiparity and degenerative spondylolisthesis but incidence of it among women down age 50 supports that multiparity has an important role that we have to consider about. So, the health education and public awareness programs have to be forced and improved specially for mothers about this particular issue and get practical steps in order to help them in decreasing their low back pains which is the most common problem among Afghan women.